O‘QUVChILARDA KASBIY TANLOV NAMOYON BO‘LIShINING PSIXOLOGIK XUSUSIYATLARI - Abdulmadjidova, M.D. (SCIENCE and SOCIETY, 2025)
This article explores the psychological characteristics of the career choice process among students. The interrelation between career choice, personal development, academic motivation, and social factors is analyzed. The study involved 120 students aged 16–18 and applied several psychological methods to assess their levels of career inclination and academic motivation. The results indicated that students with a high level of career inclination also demonstrated high academic motivation. The author emphasizes the necessity of guiding students toward suitable careers through psychological diagnostics and counseling services and highlights the critical role of school psychologists and parents in this process.